Orientasi Dominasi Sosial dengan Kekerasan dalam Pacaran pada Remaja - Rema Vara Indry Dubu; M. Dinah Ch. Lerik; R. Pasifikus Christa Wijaya; Luh Putu Ruliati (Universitas Nusa Cendana, 2020)
Abstract. This study aims to know the relationship between social dominance orientation with dating violence in adolescents. The hypothesis is that there is a positive relationship between social dominance orientation with dating violence in adolescents. Participants in this study were 400 adolescents in Kupang City (200 girls dan 200 boys) using convenience sampling. This research uses the quantitative approach with Social Dominanca Orientation7 (ODS7) adaptation scale and Conflict in Adolescent Dating Relationships Inventory (CADRI) adaptation scale as data collection methods. The hypotesys’s result using Spearman correlation technique obtained that correlation coefficient in this study is 0,102 with a significance level is 0,042 (p < 0,05). The data shows that there is a significant positive relationship between the social dominance orientation with dating violence in adolescents in Kupang city. It means that the higher social dominance orientation of adolescent, the higher tendency to commit violence in dating relationship, and vice versa. Keywords: Social Dominance Orientation, Dating Violence, Adolescent